Multicultural Education in Kindergarten – Inclusion of Children With Different Language and/or Culture (Training and Practice : Journal of Educational Sciences, 2021)
One of the many challenges of the ever-changing world of the 21st century is the emergence of multicultural societies, where children from families with different cultural identities and mother tongues are entering the educational institutions of different countries. In my research, I will explore how kindergarten teachers in Hungary encounter children with different cultural identities in their work, what knowledge they have in the field of multicultural education, and whether they have the appropriate methodological tools to implement. Furthermore, I examined how families of other cultural identities experience the introduction to Hungarian kindergartens, whether their culture is reflected in the institution.